1988
DOI: 10.1109/16.7414
|View full text |Cite
|
Sign up to set email alerts
|

Large on/off current ratio and low leakage current poly-Si TFTs with multichannel structure

Abstract: High-performance thin-film transistors (TFT's) have been thricated on a quartz substrate by the use of a laser-annealed multiple-strip-structure poly-Si film as a semiconductor. By recrystallization of a multiple-strip-structure poly-Si with CW-Ar laser, the carrier trap density of poly-Si can he reduced to obtain the preferential characteristics of a TFT. So, these poly-Si TFT's have n-channel enhancement-mode characteristics with threshold voltage as low as 0.4 V and large transconductance. Furthermore, a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, the applications of Ni-MILC poly-Si TFTs remain limited, because the grain boundaries of poly-Si in the channel region substantially degrade performance. The electrical characteristics of the TFTs can be improved by reducing the number of defects in the poly-Si grain boundaries in the channel, and poly-Si TFTs with several multichannels have been reported to effectively reduce grain boundary defects [3], [4]. The Ni-MILC poly-Si TFT suffers from higher leakage current because of Ni contamination during MILC annealing [2], [5], [6] than those by solid phase crystallization and laser crystallization.…”
Section: Reduction Of Leakage Current In Metal-inducedmentioning
confidence: 99%
“…However, the applications of Ni-MILC poly-Si TFTs remain limited, because the grain boundaries of poly-Si in the channel region substantially degrade performance. The electrical characteristics of the TFTs can be improved by reducing the number of defects in the poly-Si grain boundaries in the channel, and poly-Si TFTs with several multichannels have been reported to effectively reduce grain boundary defects [3], [4]. The Ni-MILC poly-Si TFT suffers from higher leakage current because of Ni contamination during MILC annealing [2], [5], [6] than those by solid phase crystallization and laser crystallization.…”
Section: Reduction Of Leakage Current In Metal-inducedmentioning
confidence: 99%
“…However, the applications of Ni-MILC poly-Si TFTs remain limited, because the grain boundaries of poly-Si in the channel region T.-C. Chang is with Department of Physics and Institute of Electro-Optical Engineering, Center for Nanoscience and Nanotechnology, National Sun Yat-Sen University, Kaohsiung substantially degrade performance. The electrical characteristics of the TFTs can be improved by reducing the number of defects in the poly-Si grain boundaries in the channel, and poly-Si TFTs with several multichannel have been reported to effectively reduce grain boundary defects [3], [4]. The Ni-MILC poly-Si TFT suffers from severe leakage current because of Ni contamination during MILC annealing [2], [5], [6], which is directly related to the lateral electrical field in the drain depletion region in the off-state.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is very essential to minimize the grain boundary defects in order to improve the electrical characteristics of poly-Si TFTs. It has been reported that the poly-Si TFTs with several multichannels can effectively reduce the grain boundary defects [5]- [7]. Moreover, the TFT characteristics are dramatically improved with a reduced channel width, particularly when the channel width is close to the grain size [8], [9].…”
Section: Introductionmentioning
confidence: 99%